The autobiographical interview in the continuing education of pedagogy practioners - Andrea Spano (Firenze University Press, 2024)
Sudden social transformations require education professionals to have flexible tools, in order to self-produce knowledge and new professional skills. This short article argues the use of autobiographical interview as a device for the Continuing Education. In the first instance, the reciprocity and the circularity between third-person tale and autobiography is discussed. Secondly, the focus of the reflections moves onto the potential of autobiography, that also consists in creating a new culture about society and the differences that characterize the complexity of our world. Therefore, in accordance with the previous reflections, the use of autobiographical interview collection methods is proposed to support the professional development of educators, educational designers, and pedagogical counsellors. In fact, it is argued that the use of such tools can allow one to learn several aspects regarding different life conditions, to co-construct a Grounded Theory on the phenomena and to support a positive educational relationship.   L'intervista autobiografica nell'educazione permanente delle professionalità pedagogiche. Le repentine trasformazioni sociali richiedono ai professionisti dell'educazione degli strumenti flessibili per autoprodurre conoscenza e nuove competenze professionali. In questo articolo breve si promuove l'intervista autobiografica come dispositivo dell'educazione continua. In prima battuta si affronta il rapporto di reciprocità e circolarità tra racconto e autobiografia. Successivamente, l'attenzione si sposta sul potenziale dell'autobiografia, che include la possibilità di creare una nuova conoscenza della società delle differenze che caratterizzano la complessità del nostro mondo. Pertanto, si propone l'ausilio dei metodi di raccolta delle interviste autobiografiche per sostenere lo sviluppo professionale degli educatori, dei progettisti educativi e dei consulenti pedagogici. Infatti, si sostiene che l'uso di tali strumenti può consentire di apprendere numerosi aspetti riguardanti le differenti condizioni di vita, di co-costruire una Grounded Theory sui fenomeni e di sostenere una relazione educativa positiva.